Curadoria museológica de microfósseis a coleção de Ictiólitos do Museu Paraense Emilio Goeldi - SANTOS, Christiane Sofhia Godinho (2019)
This research is a study of case concerning to the curatorship processes used in microfossils collections, more specifically Ichthyolits - microscopic skeletal fragments of fish -, it has as objective the development of a protocol for storage and documentation of these samples in paleontology collections, based on MPEG's collection. Therefore, the research relied not only on the Preventive Conservation and Museology Documentation principles, but also on interviews with researchers and curator who work with microfossils as a way to understand the specificities of this kind of collection. The Ichthyolits from MPEG's paleontology collection are more than 2.000 specimens registered by allotment, inappropriately disposed in excavated blades inside cardboard boxes, which became difficult to handling, facilitating the loss and disabling individual access to the samples. And then, forms of storage, fixers and documentation for this collection were analyzed. The samples were glued on checkered blades, using standard adhesive with PVA as a base - a easy access fixer that allows the removal of the material of the blades without causing damage. Cataloging records were produced for documentation containing general information and also specific ones, enabling the access to the material without constant handling besides the registry of it. A Protocol for the Curator of Vertebrate Microfossils - Ichthyolits were elaborated with these practices, in order to help works related to this type of collection and standardize curatorship actions related to the subjects discussed. The use of these curatorship techniques were important to promote the custody and Amazonia's fossiliferous heritage conservation, turning possible a better way to preserve the microfossils, the access to the collection and also the availability of documents for research.